A Deep Dive on Sentiments of Twitter Users During the Official Campaign Period of the 2022 Philippine Elections - King, Riana Joy S.; Ronquillo, Angeline L.; Yabut, Justin Cedric V.; Professor Joseph Ryan Lansangan (2024)
ABSTRACT

With their rapid increase in usage, social media platforms, like Twitter (now known as X), are now extended battleground for political campaigns. In this paper, the researchers studied the sentiment of Twitter account towards the top two presidential candidates in the 2022 Philippine Elections - Mr. Ferdinand Marcos Jr. and Atty. Leni Robredo - taking into account the presence of and possible sentiments bias from trolls. What is different from this approach is that the researchers analyzed sentiments on a Twitter account level, a departure from the classic tweet level analysis. Using Latent Dirichlet Allocation (LDA), it was identified that more than half of the resulting latent topics from Twitter during the campaign period focused on Atty. Leni Robredo. Through the use of an unsupervised clustering technique called hierarchical density-based spatial clustering of applications with noise (HBDBSCAN)--a procedure not usually performed together with sentiments analysis--certain accounts were tagged as potentially exhibiting troll-like behavior. Key troll characteristics include minimal topic variation and limited lexical diversity in their tweets. Additionally, utilizing Valence Aware Dictionary and Sentiments Reasoner (VADER), analysis of selected Twitter accounts showed a 92.88% general positive sentiment overall. A joint topic-sentiment metric is introduced by the researchers to further analyze the sentiment variations over a time interval, highlighting Robredo's significant lead over Marcos, and assess the effects of accounts with troll-like behaviors. Lastly, the study was able to conclude that more misleading accounts correlate with greater influence on perceived online sentiments.
Includes bibliographic references.